The Hubungan Obesitas dengan Kejadian Kolelitiasis di RSUP Dr. M. Djamil Padang Periode Januari – Desember 2019 - Muhammad Adzka Putra Anbiar; Avit Suchitra; Desmawati Desmawati (Fakultas Kedokteran, Universitas Andalas, 2022)
Background: Obesity is a common problem that occurs wich continues to increase and risk factor for cholelithiasis which can cause morbidity in cholelithiasis patients. Objective: This study aimed to determine the association between obesity and cholelithiasis and knowing the frequency distribution of patients based on age, gender and BMI. Methods: This research was an observational analytic with a case-control design with matched for age and sex. This research was held from December 2020 to March 2021 in the Medical Record Installation of RSUP Dr. M. Djamil Padang with total sample of 88 patients using simple random sampling technique. Results: The results showed that out of 44 cholelithiasis patients, as many as 28 patients (63.6%) were obese. Most were ³40 years old, 34 patients (77.3%), particularly in the age group 40-49 years with 14 patients (31.8%). Most of cholelithiasis patients were female with 28 patients (63.6%) and BMI ³25 were 28 patients (63.6%). Based on the Chi-square test, there was a relationship between obesity and the incidence of cholelithiasis (p = 0.019). Conclusion: The conclusion of this study states that there is a significant relationship between obesity and the incident of Cholelithiasis at RSUP Dr. M. Djamil Padang for the period of January-December2019.